Penerapan Taksonomi Bloom dalam Nilai-Nilai Islam (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The goal of Islamic education focuses not only on improving cognitive abilities, but also on the formation of a complete human being (insan kamil) who integrates knowledge, attitudes, spirituality, and life skills based on Islamic values. This article aims to examine the relevance of Bloom's Taxonomy in the context of Islamic education, particularly its application to Islamic values ​​in educational institutions. This research uses a literature study method with a descriptive qualitative approach through analysis of classical and contemporary literature. The results show that the three main domains in Bloom's Taxonomy—cognitive, affective, and psychomotor—are aligned with the goals of Islamic education. The cognitive domain, as implied in Q.S. Al-'Alaq: 1–5, emphasizes the importance of reading, understanding, and critical thinking as forms of intellectual development. The affective domain is related to the formation of noble character, sincerity, and self-control (Q.S. Al-Syu'ara: 88–89), which serve as the moral foundation of students. Meanwhile, the psychomotor domain emphasizes the application of Islamic values ​​in real behavior through worship, discipline, and social responsibility. The integration of these three domains reflects a holistic approach to Islamic education that balances intellectual, spiritual, and moral aspects. Thus, Bloom's Taxonomy can be used as an integrative learning model that enriches the Islamic education process and strengthens its role in character and civilization formation. Consequently, Islamic educators need to develop learning strategies that not only measure cognitive abilities but also foster students' religious attitudes and skills, leading to individuals of faith, knowledge, and noble character.